Identification of remnants of World War II air campaign for spatial management using geophysical methods (Koźle Basin, Southern Poland) - Waga, Jan M.; Sendobry, Kazimierz; Jochymczyk, Krzysztof; Pierwioła, Jolanta; Grabiec, Mariusz; Szypuła, BartłomieJ; Dolejš, Martin; Fajer, Maria (Quaestiones Geographicae, 2025)
Undiscovered military explosives pose a social and environmental burden in every war-affected country. Until recently, the methods and techniques for detecting such ordnance were limited, leaving areas vulnerable to possible fatal accidents and consecutive environmental pollution. To avoid such consequences, effective detection of unexploded ordnance (UXO) is necessary, especially in areas with intensive economic activity. This study aims to develop a viable solution for UXO detection by utilizing a range of currently available methods in various environmental conditions. Such conditions were met in the study area of the Koźle Basin (Poland, Central Europe), which was affected by massive Allied strategic bombing in 1944. It is estimated that the area contains 4,000 to 6,000 pieces of UXO. In addition, the study area has diverse environmental conditions, including dry, wet, and swampy areas, as well as various types of land cover. During the two years, the respective study sites were explored using ground penetrating radar, proton magnetometry, magnetic anomaly detection, electrical conductometry, and electrical resistivity tomography. Based on the field surveys and data analysis, we conclude that the use of conductivity meters that can be easily operated on site (especially the CMD-Explorer, which indicates the depth range of potential UXBs in addition to their location on the map) yielded very good results. The ground penetrometer radar (GPR) and the electrical resistivity method were found to be more demanding at the stage of the measurement preparation phase, both proved to be effective. The ferromagnetic characteristics of the finds were confirmed with a proton magnetometer, which was also used for preliminary field prospecting.